Chromosomal circularization of the model Streptomyces species, Streptomyces coelicolor A3(2). Issue 2 (23rd August 2013) - Nindita, Yosi; Nishikawa, Tomoya; Arakawa, Kenji; Wang, Guojun; Ochi, Kozo; Qin, Zhongjun; Kinashi, Haruyasu
Abstract Streptomyces linear chromosomes frequently cause deletions at both ends spontaneously or by various mutagenic treatments, leading to chromosomal circularization and arm replacement. However, chromosomal circularization has not been confirmed at a sequence level in the model species, Streptomyces coelicolor A3(2). In this work, we have cloned and sequenced a fusion junction of a circularized chromosome in an S. coelicolor A3(2) mutant and found a 6‐bp overlap between the left and right deletion ends. This result shows that chromosomal circularization occurred by nonhomologous recombination of the deletion ends in this species, too. At the end of the study, we discuss on stability and evolution of Streptomyces chromosomes.